PJMHS 2022
DOI: 10.53350/pjmhs22163883
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice among Women Regarding Postnatal Exercises; A Cross-Sectional Study Across Lahore in Private Sector

Abstract: Objective: This study is aimed to assess knowledge, attitude and practice among women regarding post-natal exercises. Methodology: A cross sectional study was conducted across private sector in the gynecological and obstetrical department of Punjab Social Security Hospital, Ittefaq Hospital, Hameed Latif Hospital and Khair-un-Nisa Hospital. Through non-probability convenient sampling, 120 postpartum mothers were chosen. A structured questionnaire was used to collect socio-demographic and gynecological data, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a recent study, it was reported findings of knowledge attitude and practices regarding postnatal exercises of participants from private hospitals from Lahore Pakistan. Majority of the females had knowledge of postnatal exercise, but they were not fully aware of the benefits of PNE's 10 . -----------------------------------------------------------------------------------------Received on 07-08-2022 Accepted on 19- This recent study from Lahore, Pakistan has addressed the post natal exercises; still there is need to study the PFME's during antenatal period.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, it was reported findings of knowledge attitude and practices regarding postnatal exercises of participants from private hospitals from Lahore Pakistan. Majority of the females had knowledge of postnatal exercise, but they were not fully aware of the benefits of PNE's 10 . -----------------------------------------------------------------------------------------Received on 07-08-2022 Accepted on 19- This recent study from Lahore, Pakistan has addressed the post natal exercises; still there is need to study the PFME's during antenatal period.…”
Section: Introductionmentioning
confidence: 99%
“…However, compliance with pelvic floor exercises may vary across nations depending on the level of knowledge and its perceived benefits [14]. Studies from developing countries such as Thailand, Malaysia, and Pakistan have reported that most pregnant women know about pelvic floor muscle training and consider it beneficial for their health [4,15,16,17]. However, despite having good knowledge, Pakistani pregnant women have poor attitudes and practices regarding such exercises [16,17].…”
Section: Introductionmentioning
confidence: 99%